Psychoactive Effects of Lactobacillus johnsonii BS15 on Preventing Memory Dysfunction Induced by Acute Ethanol Exposure Through Modulating Intestinal Microenvironment and Improving Alcohol Metabolic Level - Sun, Ning; Zhu, Bin; Xin, Jinge; Li, Lianxin; Gan, Baoxing; Cao, Xi; Fang, Jing; Pan, Kangcheng; Jing, Bo; Zeng, Yan; Lv, Cheng; Zhao, Ling; et al. (Frontiers in Microbiology, 2022)
The negative effects of ethanol (EtOH) abuse on the body have been widely reported in recent years. Building on the microbiota-gut-brain axis hypothesis, our study aimed to demonstrate the potential psychobiotic role of Lactobacillus johnsonii BS15 in the preventive effects of acute EtOH intake on memory impairment. We also determined whether L. johnsonii BS15 intake could effectively improve resistance to acute drinking and alleviate the adverse effects of EtOH. Male mice were fed L. johnsonii BS15 orally with (Probiotic group) or without (Control and Alcohol groups) daily dose of 0.2 × 109 CFU/ml per mouse for 28 days. Gavage with L. johnsonii BS15 significantly modified the ileal microbial ecosystem (assessed by 16S rRNA gene sequencing) in favor of Firmicutes and Lactobacillus, indicating the ability of BS15 to restore the gut microbiota. The acute EtOH exposure model (7 g/kg EtOH per mice) was established by gavage, which was administered to the alcohol and probiotic groups on day 28 of the experiment. The L. johnsonii BS15 intake effectively reduced alcohol unconsciousness time, blood alcohol concentration, and serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels. Meanwhile, the improvement of ethanol resistance time and the activities of alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) in the liver were shown by BS15 in acute alcohol-induced mice. We found that acute EtOH exposure reduced the exploration ratio (assessed by the novel object recognition test), escape latency, number of errors (assessed by passive avoidance test), and spontaneous exploration (assessed by T-maze test) in mice, which were obviously improved by L. johnsonii BS15. In the hippocampus, L. johnsonii BS15 significantly reversed the decrease in antioxidant capacity of superoxide dismutase (SOD), malondialdehyde (MDA), and glutathione (GSH) and mRNA expression of memory-related functional proteins of brain-derived neurotrophic factor (BDNF) and cyclic ampresponse element binding protein (CREB) in the hippocampal tissue after acute EtOH exposure. In conclusion, L. johnsonii BS15 intake appears as a promising psychoactive therapy to ameliorate alcohol-mediated memory impairment by increasing EtOH metabolic levels.